Repeat instability at human minisatellites arising from meiotic recombination. - Jeffreys, A J (1998)
Little is known about the role of meiotic recombination processes such as unequal crossover in driving instability at tandem repeat DNA. Methods have therefore been developed to detect meiotic crossovers within two different GC-rich minisatellite repeat arrays in humans, both in families and in sperm DNA. Both loci normally mutate in the germline by complex conversion-like transfer of repeats between alleles. Analysis shows that inter-allelic unequal crossovers also occur at both loci, although at low frequency, to yield simple recombinant repeat arrays with exchange of flanking markers. Equal crossovers between aligned alleles, resulting in recombinant alleles but without change in repeat copy number, also occur in sperm at a similar frequency to unequal crossovers. Both crossover and conversion show polarity in the repeat array and are co-suppressed in an allele showing unusual germline stability. This provides evidence that minisatellite conversion and crossover arise by a common mechanism, perhaps by alternative processing of a meiotic recombination initiation complex, and implies that minisatellite instability is a by-product of meiotic recombination in repeat DNA. While minisatellite recombination is infrequent, crossover rates indicate that the unstable end of a human minisatellite can act as a recombination warm-spot, even between sequence-heterologous alleles.